Towards social network based ontology evolution wiki for an ontology evolution - Aseeri, Ahmed; Wongthongtham, Pornpit; Wu, Chen; Hussain, Farookh Khadeer (Association for Computing Machinery (ACM), 2008)
There is a lack of well-maintained ontologies thus ontology evolution now becomes an important filed of ontology research. The evolution may reflect new categories of systems being evaluated on broader and different understandings of certain concepts and relations. Alternatively ontologies evolve because the conceptualization improves. For ontology evolution, we focus in this paper a social network based approach in which the user community has direct control over the evolution of the ontologies. Ontologies can be enriched, learnt, and obtained from social network users using various empirical techniques. In this paper, we ground the social network based approach on the philosophy of wikis so called ontology Evolution Wiki.